Comparison of Two Powder Processing Techniques on the Properties of Cu-NbC Composites - Long, B.D.; Othman, R.; Zuhailawati, H.; Umemoto, M. (Hindawi Publishing Corporation, 2014)
An in situ Cu-NbC composite was successfully synthesized from Cu, Nb, and C powders using ball milling and high pressure torsion (HPT) techniques. The novelty of the new approach, HPT, is the combination of high compaction pressure and large shear strain to simultaneously refine, synthesize, and consolidate composite powders at room temperature. The HPTed Cu-NbC composite was formed within a short duration of 20 min without Fe contamination from the HPT’s die. High porosity of 3–9%, Fe and niobium oxidations, from grinding media and ethanol during ball milling led to low electrical conductivity of the milled Cu-NbC composite. The electrical conductivity of the HPTed Cu-NbC composite showed a value 50% higher than that of milled Cu-NbC composite of the same composition.